11.- THE DIATOPIC VARIANTS CUSCO, ZAINO, CHIRU AND ILHÉU IN BRAZILIAN PORTUGUESE - Rodrigues dos Santos, Dayse (Nueva Revista del Pacífico, 2021)
Abstract: The diatopic variants of lexical level present in Brazilian Portuguese are present throughout the territory. Thus, the occurrences of common variants in southern Brazil were analyzed in the short stories Trezentas onças and Melancia - Coco verde from the work Contos gauchescos (1976), by João Simões Lopes Neto, in the light of variationist sociolinguistics and dialectology. The objective is to appreciate how the lexical items cusco, zaino, chiru and ilhéu converge in this type of linguistic variation in comparison with Brazilian Portuguese standard. After reviewing the bibliography on variationist sociolinguistics and dialectology, the most categorical passages were selected in which the four words appear to weave more in-depth reflections, performing the qualitative character of this research. As a result, we verify the way in which the southern literary language illustrated the dialect in this textual production. Resumen: Las variantes diatópicas de nivel léxico presentes en el portugués brasileño están presentes en todo el territorio. Así, las ocurrencias de variantes comunes en el sur de Brasil fueron analizadas en los cuentos Trezentas onças y Melancia - Coco verde de la obra Contos gauchescos (1976), de João Simões Lopes Neto, a la luz de la sociolingüística y dialectología variacionista. El objetivo es apreciar cómo los ítems léxicos cusco, zaino, chiru y ilhéu convergen en este tipo de variación lingüística en comparación con la variación estándar del portugués brasileño. Tras revisar la bibliografía sobre sociolingüística y dialectología variacionista, se seleccionaron los pasajes más categóricos en los que las cuatro palabras parecen tejer reflexiones más profundas, realizando el carácter cualitativo de esta investigación. Como resultado, comprobamos la forma en que la lengua literaria sureña ilustró el dialecto en esta producción textual.